Genital tract function in men with Noonan syndrome. Issue 6 (June 1994) - Elsawi, M M; Pryor, J P; Klufio, G; Barnes, C; Patton, M A
Abstract : In order to study the pattern of male fertility in Noonan syndrome, and its potential implications for genetic counselling, the genital tract function was studied in 11 adult males with Noonan syndrome. Bilateral testicular maldescent occurred in six. The mean testicular volume was 21 (SD 4) ml. The stretched flaccid penile length was 11.4 (SD 1.2) cm. Puberty was delayed in three. Four of the men had fathered children. The LH and testosterone levels were essentially normal in all men, while the FSH levels were grossly raised in the group with testicular maldescent, with the exception of one man. Semen samples were obtained from five men, and azoospermia or oligozoospermia was present in four of them. Sexual function is not affected in men with Noonan syndrome, but the onset of sexual activity was delayed in men with late onset of puberty. Bilateral testicular maldescent appears to be the main factor contributing to impairment of fertility in men with Noonan syndrome.